Influence of contextual factors on quality of primary care in children with asthma. Issue 3 (21st November 2018) - Ingemansson, Maria; Jonsson, Marina; Henriksson, Peter; Hedlin, Gunilla; Kull, Inger; Wikström Jonsson, Eva; Krakau, Ingvar; Kiessling, Anna
Abstract: Objective: Asthma is a common chronic disease among children, quality assurance is thus important. Adherence to pre‐specified quality indicators of practice guidelines could be used to assess the quality of asthma care. The aim was to estimate which contextual factors that had an influence on the primary health care centres (PHCs) adherence to the quality indicators as stated in the practice guidelines. Method: A pragmatic cross‐sectional study was performed comprising 14 PHCs in Sweden. Included contextual factors were socio‐demographic characteristics, organizational characteristics, and indicators regarding engagement in asthma care. Documentation on adherence to the quality indicators was retrieved from the medical health care records. Quality indicators included documentation of history of allergy and risk factors, diagnostics and patient support performed, and pharmacological treatment. To score adherence, a composite quality indicator (CQI) was computed for each PHC. A multivariable regression analysis was performed by orthogonal projection to latent structures (OPLS). By this analysis, the relationship between the result variable (CQI) and 26 pre‐specified contextual factors was assessed. Results: There was a wide variation of CQI between the PHCs. The OPLS analysis identified that 10 of the contextual factors influenced CQI. The most pronounced influences were found in more time scheduled for asthma care, a lower age‐limit for performing spirometry, a lower duty‐grade for general practitioners, and a higher activity at asthma educational seminars. We found no influence of socio‐demographic contextual factors. Conclusion: We found that some of the contextual factors at the PHCs influenced the quality of performed care. Evidence‐based care in paediatric asthma may thus be presumed to be facilitated by allocating time, by improving interprofessional collaboration, and by creating structures and opportunities for commitment to asthma care.